2006
DOI: 10.1300/j190v02n04_08
|View full text |Cite
|
Sign up to set email alerts
|

Use of Collateral Contacts in Child Custody Evaluations

Abstract: Four hundred nineteen members of the Association of Family and Conciliation Courts (AFCC) identify themselves as custody evaluators in the 1999-2000 membership directory. One hundred of these custody evaluators were randomly selected for inclusion in this survey of the use of collateral contact interviews in child custody evaluations. Fifty-three of those selected responded to a brief questionnaire concerning their use and views of collaterals. All evaluators reported use of the collateral interview. Most prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…One hundred per cent of the custody evaluators surveyed by Kirkland, McMillan, and Kirkland (2005) reported relying on collateral interviews, and Bow and Quinnell (2001) found in a survey that over three-quarters of child custody evaluators reported interviewing therapists, new spouses or live-in partners, and teachers, with the mean time spent conducting interviews ranging from 0.62 hours with teachers to 1.46 hours with spouses/live together partners. When sexual abuse (Bow et al, 2002) or domestic violence (Bow & Boxer, 2004) allegations are involved, child custody evaluators report having some contact with law enforcement professionals or physicians over 90% of the time.…”
Section: Professionals' Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred per cent of the custody evaluators surveyed by Kirkland, McMillan, and Kirkland (2005) reported relying on collateral interviews, and Bow and Quinnell (2001) found in a survey that over three-quarters of child custody evaluators reported interviewing therapists, new spouses or live-in partners, and teachers, with the mean time spent conducting interviews ranging from 0.62 hours with teachers to 1.46 hours with spouses/live together partners. When sexual abuse (Bow et al, 2002) or domestic violence (Bow & Boxer, 2004) allegations are involved, child custody evaluators report having some contact with law enforcement professionals or physicians over 90% of the time.…”
Section: Professionals' Practicesmentioning
confidence: 99%
“…All of these collateral contacts may provide potentially valuable information about the functioning of the parents and children in a variety of settings. Kirkland et al (2005) reported that 81% of child custody evaluators they surveyed reported using telephone and face-to-face interviews with collateral sources, whereas 16% indicated only using phone interviews and an even smaller number reported providing the collateral contact with a form to complete. Each type of data gathering offers distinct advantages and disadvantages.…”
Section: Third Party Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…AFCC, 2007;APA, 1991APA, , 1994. In a nationwide survey of experienced custody evaluators who are members of AFCC, Kirkland et al (2005) found that 100% reported using collateral interviews in their evaluations.…”
Section: Steps In Collecting Collateral Informationmentioning
confidence: 99%
“…A number of experienced forensic psychologists have discussed these guidelines for choosing sources (e.g., Austin, 2002;Gould, 1998Gould, , 1999bGould, , 2006Kirkland et al, 2005;Skafte, 1985). 32.…”
mentioning
confidence: 99%